E-Commerce as a Trading Facility of Batu Bara Typical Songket Crafts in Padang Genting Village - Ferdinanda Satria Hammadi; Januarizkah Napitu; Novel Laura Samanta; Tia Apriyani; Alfonsus Manalu; Geraldo Christofer L. Tobing; Ummi Kalsum Siregar; Fadhila Hafizah; Intan Faadhilah; Bill Sahata Nanggaraja Purba; Adetya Ramadhan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of writing this article is to create a solution to the problems experienced by songket craftsmen in Padang Genting Village who have difficulty marketing songket because the process of making songket is quite long and dependent on distributors. The village which is officially a weaving village or village is the producer of Batu Bara Malay songket cloth on December 19 2019 in Padang Genting Village, Talawi District, Batu Bara Regency. We carry out this activity through seminars on the use of e-commerce as a means of buying and selling songket online and class discussions with songket craftspeople in Padang Genting Village with the aim of increasing the knowledge, insight, and skills of songket craftsmen in marketing and advertising songket online. The results obtained from these seminars and class discussions are the addition of the knowledge of songket craftsmen in marketing their products online, and songket craftsmen now have online shops to market their products to various regions.